'Fake news' as infrastructural uncanny. (February 2020) - Gray, Jonathan; Bounegru, Liliana; Venturini, Tommaso
In this article, we examine how the social disturbance precipitated by 'fake news' can be viewed as a kind of infrastructural uncanny. We suggest that the threat of problematic and viral junk news can raise existential questions about the routine circulation, engagement and monetisation of content through the Web and social media. Prompted by the unsettling effects associated with the 'fake news' scandal, we propose methodological tactics for exploring (1) the link economy and the ranking of content, (2) the like economy and the metrification of engagement and (3) the tracker economy and the commodification of attention. Rather than focusing on the misleading content of junk news, such tactics surface the infrastructural conditions of their circulation, enabling public interventions and experiments to interrogate, challenge and change their role in reconfiguring relations between different aspects of social, cultural, economic and political life.